Веб-сервіс для агрегації контенту підписок із соціальних мереж - Міллер, П. П. (ХНУРЕ, 2019)
In this work, the main object of Web service for aggregating content of subscriptions from social networks. Purpose of the development to design and create system that unites specified content from different social networks into custom categories, keeps it in one place and one format and makes it easy to surf and comfortable to read. A software implementation of the Web service was designed and created as a result of the development. It allows the user to collect the content from various sources in one place.